2006
DOI: 10.1074/jbc.m508915200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ABCG1, but Not ABCA1, Correlates with Cholesterol Release by Cerebellar Astroglia

Abstract: Central nervous system lipoproteins mediate the exchange of cholesterol between cells and support synaptogenesis and neuronal growth. The primary source of lipoproteins in the brain is astroglia cells that synthesize and secrete apolipoprotein (apo) E in high density lipoprotein-like particles. Small quantities of apoA1, derived from the peripheral circulation, are also present in the brain. In addition to the direct secretion of apoE-containing lipoproteins from astroglia, glia-derived lipoproteins are though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 46 publications
6
88
1
Order By: Relevance
“…With its expression in liver and brain, ABCB1 -the prototype of the B subclass of transporters -and ABCA1 regulate the high-density lipoprotein levels in the plasma and cholesterol contents of several cell types in these organs [106][107][108][109][110][111][112][113][114]. Most interestingly, the ABCB1 transporter also shows strong expression in neurons of the hippocampus formation, particularly in the granule cells of the DG [85].…”
Section: Abc Transporters In the Brainmentioning
confidence: 99%
“…With its expression in liver and brain, ABCB1 -the prototype of the B subclass of transporters -and ABCA1 regulate the high-density lipoprotein levels in the plasma and cholesterol contents of several cell types in these organs [106][107][108][109][110][111][112][113][114]. Most interestingly, the ABCB1 transporter also shows strong expression in neurons of the hippocampus formation, particularly in the granule cells of the DG [85].…”
Section: Abc Transporters In the Brainmentioning
confidence: 99%
“…GAPDH, 18S or CycA (Abildayeva et al, 2006;Karten et al, 2006;Liang et al, 2004). Recently, suitable reference genes were described for rat brain tissue and hippocampal neurons under different experimental conditions (Bonefeld et al, 2008;Langnaese et al, 2008;Santos and Duarte, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies failed to detect any effect of ABCG1 overexpression or deficiency on cholesterol efflux and brain lipid levels in apoE deficient (Burgess et al, 2008a) and PDAPP transgenic mice (Burgess et al, 2008b), others report positive correlations between ABCG1 expression and peripheral lipid tissue levels (Kennedy et al, 2005). ABCA1 has repeatedly been reported to act in concert with ABCG1, and both were shown to act sequentially in promoting phospholipids and cholesterol efflux from peripheral cell and to facilitate apoE-HDL lipidation (Gelissen et al, 2006;Karten et al, 2006;Kennedy et al, 2005;Vaughan and Oram, 2006). Cholesterol loading in vitro enhances ABCG1, but not ABCA1, expression and correlates best with cholesterol efflux from astrocytes (Karten et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…ABCG1 has been associated with intracellular cholesterol trafficking and efflux (Abildayeva et al, 2006;Burgess et al, 2008aBurgess et al, , 2008bKarten et al, 2006;Klucken et al, 2000;Vaughan and Oram, 2005), whereas ABCA1 has been linked to secretion and lipidation of apoA1 with cholesterol and HDL production in the plasma, CSF and brain (Hirsch-Reinshagen et al, 2004;Koldamova et al, 2003;Wahrle et al, 2004). Furthermore, in vitro work demonstrated that the coordinated action of ABCA1 and G1 is required for optimal removal of cellular cholesterol (Gelissen et al, 2006;Vaughan and Oram, 2006).…”
Section: Introductionmentioning
confidence: 99%